A veritable tower of Babel: on the confusion between the legal and economic interpretations of Article 101(3) of the Treaty on the Functioning of the European Union. (2nd September 2015) - Baarsma, Barbara; Rosenboom, Nicole
Abstract : The current system of exemptions from the cartel prohibition (Article 101(3) TFEU) is a veritable tower of Babel. For one, there is a considerable confusion of tongues between jurists and economists on the goal of competition law. Moreover, the European Commission's Guidelines on the application of the cartel prohibition explain the law differently from what is apparent from the case law. This economic paper aims to reduce the confusion of tongues by answering questions such as: what is consumer welfare, what is public interest, and should non-competition public interests be included in the assessment of competition cases? Actual cases are used to show the terminology of competition and other public interests. We develop a framework for balancing the economic benefits produced by restrictive agreements against the restrictive effects of these agreements.